Reconstruction of the Understanding of Nasikh, Mansukh, and Ayatul Mutasyabbihat in a Modern Context - Abidin, Abidin (al-Afkar, Journal For Islamic Studies, 2025)
The interpretation of the Qur'an in the modern era is faced with the challenges of social change, culture and technological progress. The concepts of Nasikh (appointment of law) and Mansukh (abolition of law) are important to ensure that the laws of the Koran remain relevant to the context of the times. Apart from that, Ayatul Mutasyabbihat or ambiguous verses also require careful interpretation. This research examines the views of classical and contemporary scholars regarding these three concepts, to ensure that the teachings of the Qur'an remain applicable and provide solutions to contemporary problems. Through a descriptive qualitative approach with a literature review, the research results show that a correct understanding of Nasikh, Mansukh, and Ayatul Mutasyabbihat is very important to avoid misinterpretations and ensure that the teachings of the Qur'an remain relevant and provide solutions to the challenges faced by Muslims in the contemporary era.